Ecotype Differentiation in the Face of Gene Flow within the Diving Beetle Agabus bipustulatus (Linnaeus, 1767) in Northern Scandinavia - Drotz, Marcus K.; Brodin, Tomas; Saura, Anssi; Giles, Barbara E. (PLOS ONE, 2012)
The repeated occurrence of habitat-specific polyphyletic evolved ecotypes throughout the ranges of widely distributed species implies that multiple, independent and parallel selection events have taken place. Ecological transitions across altitudinal gradients over short geographical distances are often associated with variation in habitat-related fitness, these patterns suggest the action of strong selective forces. Genetic markers will therefore contribute differently to differences between ecotypes in local hybrid zones. Here we have studied the adaptive divergence between ecotypes of the water beetle Agabus bipustulatus along several parallel altitudinal gradients in northern Scandinavia. This water beetle is well known for its remarkable morphological variation associated with mountain regions throughout the western Palaearctic. Two morphological ecotypes are recognised: a montane type with reduced flight muscles and a lowland type with fully developed muscles. Using a multilocus survey of allozyme variation and a morphological analysis with landmark-based morphometrics, across thirty-three populations and seven altitudinal gradients, we studied the local adaptive process of gene flow and selection in detail. Populations were sampled at three different elevations: below, at and above the tree line. The results indicate that the levels of divergence observed between ecotypes in morphology and allele frequencies at α-Glycerophosphate dehydrogenase relative to those shown by neutral molecular markers reflects local diversifying selection in situ. Four main lines of evidence are shown here: (1) A repeated morphological pattern of differentiation is observed across all altitudinal transects, with high reclassification probabilities. (2) Allele and genotype frequencies at the α-Gpdh locus are strongly correlated with altitude, in sharp contrast to the presumable neutral markers. (3) Genetic differentiation is two to three times higher among populations across the tree line than among populations at or below. (4) Genetic differentiation between ecotypes within independent mountain areas is reflected by different sets of allozymes.